Thermal analysis of a white calcium bentonite - BAYRAM, HALE (SPRINGER, 2010)
A white calcium bentonite (CaB) taken from CamlA +/- dere (Ankara, Turkey) region was heated at various temperatures between 100 and 1100 A degrees C for 2 h. The mineralogy of the CaB was determined as calcium smectite (CaS), metahalloysite (MH), opal-A (OA), opal-CT (OCT), quartz (Q), feldspar (F), and calcite (C) using the X-ray diffraction patterns of the natural CaB and its heated samples. Besides the XRD patterns, the thermogravimetry, differential thermal analysis, and low-temperature nitrogen adsorption (N-2-AD) data show that the CaS lose adsorbed and hydration water up to 300 A degrees C, dehydroxylation takes place between 300 and 750 A degrees C, and then the 2:1 layer structure completely collapses above 900 A degrees C. The activation energies for the dehydration and dehydroxylation were calculated as 7636 and 48838 J mol(-1), respectively, from the TG data using Coats and Redfern method. The specific surface area (S) and specific micro-mesopore volume (V) obtained from N-2-AD data were 44 m(2) g(-1) and 0.100 cm(3) g(-1) for the natural CaB. S and V reach their maxima of 105 m(2) g(-1) and 0.155 cm(3) g(-1), respectively, at 300 A degrees C, remain approximately constant as the temperature increases up to 700 A degrees C and then decrease almost in parallel with each other, reaching their minima at 900 A degrees C. This indicates that the S and V values increase gradually during dehydration and dehydroxylation of the CaS.
Keywords: Activation energy; Bentonite; Dehydration; Dehydroxylation; Pore volume; Surface area; X-RAY-DIFFRACTION; SURFACE-ACIDITY; MINERAL MIXTURE; HEAT-TREATMENT; BEHAVIOR; ADSORPTION; VACANT; CLAY; MONTMORILLONITE; DEHYDROXYLATION